The Developing World Is Poorer Than We Thought, but No Less Successful in the Fight against Poverty - Chen, Shaohua; Ravallion, Martin (2012)
A new data set on national poverty lines is combined with new price data and almost 700 household surveys to estimate absolute poverty measures for the developing world. We find that 25% of the population lived in poverty in 2005, as judged by what "poverty" typically means in the world's poorest countries. This is higher than past estimates. Substantial overall progress is still indicated--the corresponding poverty rate was 52% in 1981--but progress was very uneven across regions. The trends over time and regional profile are robust to various changes in methodology, though precise counts are more sensitive.